Strategi Komunikasi Digital Melalui Media Sosial Untuk Membangun Kepercayaan Konsumen - Deva Satria Pamungkas; Indra Bahari Saputra; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The mass development of digital technology has changed the way companies communicate with consumers. One of the most effective communication channels is social media, which provides a platform for adress interaction between brands and consumers. Consumer trust is the main factor influencing purchasing decisions and brand loyalty. This articel used a qualitative approach to make a study various digital communication strategies that can build consumer trust in social media. Through social media, companies can implement various communication strategies, such as being transparent and honest in communication; active interaction with consumers; consistent in branding; consumer testimonials and reviews; compelling use of influencers; security and privacy of consumer data; and responsive to consumer problems and complaints.